A retrospective histopathological analysis with clinicoradiological correlation of gallbladder diseases in a tertiary care centre in Bihar- A retrospective study. - Rabab, Shadan; Imam, Zeenat Sarmadi; Pankaj, Deepak; Kumar, Bipin; Mandal, Manish; Muni, Sweta (Student's Journal of Health Research Africa, 2025)
Background Diseases of the gall bladder are a common health issue affecting the population worldwide. The spectrum of the disease ranges from inflammatory lesions to dysplasia and further extends to carcinomas. Histopathological examination is the gold standard diagnostic modality. The diagnostic process is amplified when histopathological findings are correlated with clinicoradiological features. Aims and objectives: The study aims to highlight the histopathological spectrum of gall bladder lesions and it’s clinicoradiological correlation, thereby advancing the understanding of gall bladder pathology and its management. Materials and methods A retrospective observational study was conducted in the Pathology department at IGIMS, Patna. Cases were selected as per the inclusion and exclusion criteria from 3100 cholecystectomy samples received from January 2021 to December 2024. Details were collected from histopathology request forms and hospital records. Gross and microscopic features were analysed, and the parameters were calculated. Results The mean age of the patient was 42minus 4.76 years, with the majority in the age group of 41 to 50 years, having a female predominance. A significant association was observed between increased gall bladder wall thickness and adenocarcinoma. Cholecystectomy performed in patients less than 10 years of age had a direct relationship with choledochal cyst. Radiological and histopathological diagnosis corroborated in 89% percent of cases. Conclusion Most gall bladder lesions have an inflammatory origin, with a female preponderance. Cholecystectomy is the treatment of choice. Increasing incidence of malignancy emphasizes the importance of thorough histopathological examination in confirming the preoperative diagnosis and simultaneously sampling any suspicious areas to rule out an incidental finding of malignancy. Recommendations Routine histopathological examination of all cholecystectomy specimens is recommended to detect incidental malignancies. Prospective studies and improved radiological protocols are needed to enhance diagnostic accuracy and patient outcomes.